The China image in Malaysian Chinese literature - Lin, D.S.; Leng, N.Y. (2010)
The ``China Image'' in the Malaysian Chinese Literature has undergone a dramatic transformation over a long period of time. First of all, what is meant by ``China''? Secondly, different views held by people with different identities help to create different versions of the ``China image''. The changes of times and minds, or perhaps the different perspectives in thought and angle of view might also lead to a different conclusion. This paper intends to analyze the ``China iamge'' from three perspectives so as to have a better understanding of the ``China image'' in the context of Malaysian Chinese Literature.